THE EFFECTIVENESS OF THINK ALOUD STRATEGY TO IMPROVE STUDENTS’ READING COMPREHENSION IN NARRATIVE TEXT STUDY AT THE EIGHTH GRADE OF SMP MUHAMMADIYAH LIMBUNG - Juniati, Juniati; Dalle, Muhammad Basri; Azis, Awalia (JKIP (Jurnal Keguruan dan Ilmu Pendidikan), 2018)
The problem of this research consisted of how is the improvement at the students’ literal and interpretative reading comprehension through Think Aloud Strategy at the eighth grade of SMP Muhammdiyah Limbung? This research aimed to find out the improvement of the students’ literal comprehension and interpretative comprehension. The research is limited to improve the students’ comprehension in narrative text through Think Aloud Strategy on literal reading comprehension (the specific information and sequence events) and interpretative comprehension (conclusion and implication). To find out the improvement, the researcher used pre-experimental design with one group pre-test and post-test design. The population was the eighth grade students of SMP Muhammadiyah Limbung. The sample was taken by purposive sampling technique and the total number of sample was 36 students. It employed of six meetings (one meeting for pre-test, four meetings for treatment, and one meeting for post-test). It employed reading test as instrument. The research findings indicated that the application of Think Aloud Strategy was effective in improving the students’ literal and interpretative reading comprehension. It was proved by the value of the t-test 19.91, which was higher than the value of t-table (2.030). This indicated that H1wasaccepted, and H0 was rejected and there was a significant difference of the students’ reading comprehension before and after using Think Aloud Strategy. It was concluded that Think Aloud Strategy improved the students’ reading comprehension.